Prevalence of Opioid and Benzodiazepine Prescriptions for Osteoarthritis. Issue 8 (11th June 2020) - Alamanda, Vignesh K.; Wally, Meghan K.; Seymour, Rachel B.; Springer, Bryan D.; Hsu, Joseph R.; ,
Abstract : Objective: Opioids and benzodiazepines are commonly used for management of osteoarthritis, despite evidence‐based recommendations to the contrary. This study aimed to quantify the prevalence of opioid and benzodiazepine prescribing for osteoarthritis. Additionally, we aimed to characterize risk factors for prescription drug misuse, abuse, and diversion among this population. Methods: We conducted a descriptive analysis of adult outpatient encounters with a primary diagnosis of osteoarthritis during a 1‐year period at a large health care system, excluding cancer and outpatient procedures. Demographic data, prescription data, and patient‐specific risk factors were collected. Descriptive analysis was conducted to characterize arthritis patients who received and did not receive prescription opioids. Results: During 1 year, our system had 31, 123 outpatient encounters for osteoarthritis. Opioids and benzodiazepines were prescribed for nearly 27% of the encounters (n = 8, 420). In all, 43% of the encounters involved patients age ≥65 years. Hydrocodone‐acetaminophen was the most common medication prescribed (34.3%). Most prescriptions were written by pain specialists (53%). A total of 35.5% of patients had a risk factor for prescription misuse, the most prevalent being early refill and a history of receiving ≥3 prescriptions in the past month. Conclusion: Prescriptions for opioids and benzodiazepines continue to be written for osteoarthritis. These prescriptions may pose a risk for adverse outcomes since >1 in 5 patients receiving prescriptions had a risk factor for misuse. Continued efforts to improve compliance with evidence‐based guidelines as well as multimodal and alternative pain management pathways are critical to help curb the use of opioids for management of osteoarthritis‐related pain. Level of evidence: level IV.